Complete Genome Sequence of an Avian Metapneumovirus Subtype B Strain from Hungary - Goraichuk, Iryna V. (Microbiol Resour Announc, 2020)
Avian metapneumoviruses (aMPVs), which have been reported in many countries, cause acute upper respiratory tract disease in chickens and turkeys. Using next-generation sequencing, we report here the complete genome sequence of an aMPV subtype B strain that was isolated from a turkey in Hungary in 1989.